Critical Discourse Analysis for Material Development for English Language Teaching in a Thai Military Academic Context - Preecha, Parinyaporn; Srinon, Udomkrit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 11 No 1 (2019): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
This paper analyses critical perspective (CP) as one of the approaches to language teaching and learning in a Thai military academic context. Regarding related perspectives from critical race theory, identity studies, social justice and critical multiculturalism, the use of the pedagogy in a Thai context stresses empowering learners in a military school to think and act critically with the aim of transforming their life conditions and enhancement of their overall for their well being. Therefore, the present study aims to explore CP including pedagogies that support the problem posing with education in a specific context, a military school; and to offer suggestions for applying problem posing as a framework for developing materials in ELT classrooms. The preliminary analysis demonstrates that the CP, despite being a new and innovative approach, can be used in educational contexts to better understand how learners learn and position themselves in their context. The study suggests that critical perspectives implemented into EFL curriculum and classrooms practices in Thai contexts which will meet the needs of diverse students.